(untitled) (Global Journal of Human-Social Science, 2019)
This study is entitled Comparison Analysis of Stock Price Before and After Announcement of Business Index 27. The target population is 27 companies, operational variables taken is the stock price 20 days before and after the announcement of business index 27. Processing data is done using SPSS Version 22 Program, the results show there is no difference in stock prices before and after announcements of business index 27 means that the announcement does not affect stock prices, but the relationship between stock prices before and after is very strong.